(untitled) (Fiep Bulletin - online, 2015)
Identify the relationship of school period with the body composition and the intensity of physical activity of prepubescent male and female children. Methods: For the study, were randomly selected 55 boys and 48 girls, age 7 to 8 years old. Anthropometrics measurements: BMI and sum of 7 skin folds. For the intensity of physical activity the children were divided in three groups according to Bouchard (1983). The physical inactivity corresponding to the values of 1 and 2 (1 to 1,5 METs); light activity 3 4 - 5 (1,6 to 3,4 METs), moderate/high activities 6 to 9 (above 3,5 METs). For data analyses, ANOVA´s two-way and Pearson moment correlations were used, with p<0,05. Results: Analyzes of variance showed significant sex differences in light activity, F= 5,89 (1,97), p=0,017 (Boys: 186,18 71,12; girls: 215,10 63,42), and for moderate/high activity F= 5,87 (1,97), p=0,017 (Boys: 100,90 51,22; girls: 80,31 39,36). For boys (r= 0,30) and children attending the afternoon school period (r= - 0,29) the correlation showed significance with the sum of skin folds. Conclusion: the results showed that girls tend to do more light activity and boys to be engaged in moderate/high activity, what might be related to less percentage o body fat. To do activities with moderate/high intensity may be a way to prevent children development of overweight and obesity.